Brian Friel, the BBC, and Ronald Mason. (November 2017) - Matthews, Kelly
Abstract : Accepted theatre history awards Sir Tyrone Guthrie a singular position of influence on Brian Friel's early career. But hundreds of documents newly discovered in BBC archives reveal that Belfast radio drama producer Ronald Mason was perhaps more important to the young playwright's initial development. Not only did Mason coach Friel on revising his scripts for radio audiences, he also introduced Friel's work to James Ellis of the Ulster Group Theatre, while singing his praises to Guthrie. In the pivotal first decade of Friel's writing life, Ronald Mason was a sincere friend and a worldly-wise supporter: exactly the advocate Friel needed.